Post-Treatment Plasma D-Dimer Levels Are Associated With Short-Term Outcomes in Patients With Cancer-Associated Stroke - Nakajima, Sho; Kawano, Hiroyuki; Yamashiro, Kazuo; Tanaka, Ryota; Kameda, Tomoaki; Kurita, Naohide; Hira, Kenichiro; Miyamoto, Nobukazu; Ueno, Yuji; Watanabe, Masao; Hirano, Teruyuki; Fujimoto, Shigeru; et al. (Frontiers in Neurology, 2022)
Background and Objective Hypercoagulability is associated with increased risks of ischemic stroke and subsequent mortality in patients with active cancer. This study investigated the relationships between plasma D-dimer levels after stroke treatment and short-term outcomes in patients with cancer-associated stroke. Methods This retrospective, observational, multicenter study analyzed consecutive patients with cancer-associated ischemic stroke. Hypercoagulability was assessed by plasma D-dimer levels before and after stroke treatment. Short-term outcomes were assessed in terms of poor outcomes (a modified Rankin Scale score >3), cumulative rates of recurrent ischemic stroke, and mortality at 30 days after admission. Results Of 282 patients, 135 (47.9%) showed poor outcomes. Recurrent ischemic stroke was observed in 28 patients (9.9%), and the cumulative mortality rate was 12.4%. Multivariate analysis showed that post-treatment plasma D-dimer levels ≥10 μg/ml were independently associated with both poor outcomes (adjusted odds ratio [OR], 9.61; 95% confidence interval [CI], 3.60–25.70; P < 0.001) and mortality (adjusted OR, 9.38; 95% CI, 3.32–26.44; P < 0.001). Pre-treatment plasma D-dimer levels ≥10 μg/ml were not associated with these outcomes. Patients who received heparin had higher pre-treatment plasma D-dimer levels than those treated with other anticoagulants. Heparin produced a significant reduction in D-dimer levels from pre- to post-treatment without increasing the incidence of hemorrhagic events. Conclusion A high plasma D-dimer level after stroke treatment was associated with poor short-term outcomes in patients with cancer-associated stroke. Using anticoagulants to reduce D-dimer levels may improve short-term outcomes in these patients.